2008
DOI: 10.1007/bf02981331
|View full text |Cite
|
Sign up to set email alerts
|

Effect of log seasonality on reproductive potential ofMonochamus galloprovincialis reared in scots pine logs under laboratory conditions

Abstract: Monochamus galloprovincialis (Olivier) is the vector of the pinewood nematode, Bursaphelenchus xylophilus (Steiner and Buhrer) Nickle, in Europe and Asia. Reproduction is probably the most important event in the life history of insects and may be affected by a number of factors, such as seasonal changes in larval or adult nutrition. In this study the effect of season on the reproductive potential of M. galloprovincialis females reared in black pine logs was investigated by constructing fertility tables for eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 25 publications
2
6
0
Order By: Relevance
“…In contrast, beetles from P. sylvestris had higher reproductive potential when emerging from spring logs compared with summer and autumn logs. Other studies revealed similar results with other Monochamus vectors studied in North America (M. carolinensis) and East Asia (M. alternatus), suggesting that these species have similar life-history patterns (Naves et al 2006a(Naves et al , 2008Akbulut et al 2007Akbulut et al , 2008aAkbulut 2009). Generally, P. sylvestris logs had a greater reproductive performance than the logs of P. nigra under laboratory conditions (Akbulut 2009).…”
Section: European Monochamus Species 41 Monochamus Galloprovincialissupporting
confidence: 72%
See 3 more Smart Citations
“…In contrast, beetles from P. sylvestris had higher reproductive potential when emerging from spring logs compared with summer and autumn logs. Other studies revealed similar results with other Monochamus vectors studied in North America (M. carolinensis) and East Asia (M. alternatus), suggesting that these species have similar life-history patterns (Naves et al 2006a(Naves et al , 2008Akbulut et al 2007Akbulut et al , 2008aAkbulut 2009). Generally, P. sylvestris logs had a greater reproductive performance than the logs of P. nigra under laboratory conditions (Akbulut 2009).…”
Section: European Monochamus Species 41 Monochamus Galloprovincialissupporting
confidence: 72%
“…Akbulut et al (2008c) found notable similarities between M. carolinensis and M. galloprovincialis in many biological characteristics, such as apparent survivorship from egg to larvae, generation survivorship and the number of adults emerged. Other studies revealed similar results with other Monochamus vectors studied in North America (M. carolinensis) and East Asia (M. alternatus), suggesting that these species have similar life-history patterns (Naves et al 2006a(Naves et al , 2008Akbulut et al 2007Akbulut et al , 2008aAkbulut 2009).…”
Section: European Monochamus Species 41 Monochamus Galloprovincialissupporting
confidence: 72%
See 2 more Smart Citations
“…Therefore, the possible introduction of the pinewood nematode and other exotic pests during forest product trade is a constant threat in Turkey. The only known potential vector of the pine wood nematode in Turkey is M. galloprovincialis; published information is very limited, with some general description and distribution details (Çanakçıoğlu and Mol 1998) and biology of M. galloprovincialis (Akbulut et al 2008a, b). It is important to study the detailed biology and ecology of M. galloprovincialis, including the potential different effects of commonly distributed host trees such as P. sylvestris and P. nigra.…”
Section: Introductionmentioning
confidence: 99%